Exocyst-mediated apical Wg secretion activates signaling in the Drosophila wing epithelium - Chaudhary, Varun (PLoS Genet, 2019)
Wnt proteins are secreted signaling factors that regulate cell fate specification and patterning decisions throughout the animal kingdom. In the Drosophila wing epithelium, Wingless (Wg, the homolog of Wnt1) is secreted from a narrow strip of cells at the dorsal-ventral boundary. However, the route of Wg secretion in polarized epithelial cells remains poorly understood and key proteins involved in this process are still unknown. Here, we performed an in vivo RNAi screen and identified members of the exocyst complex to be required for apical but not basolateral Wg secretion. Specifically blocking the apical Wg secretion leads to reduced downstream signaling. Using an in vivo ‘temporal-rescue’ assay, our results further indicate that apically secreted Wg activates target genes that require high signaling activity. In conclusion, our results demonstrate that the exocyst is required for an apical route of Wg secretion from polarized wing epithelial cells.